“Dangerous Act(s) to Society” - The Foundation for Crime, Criminal Responsibility and Punishment - Viet, Trinh Tien (VNU Journal of Science: Legal Studies, 2024)
Article 8 of the Penal Code 2015, amended in 2017, stipulates and defines the concept of crime as follows: “ Crime is an act that is dangerous to society ...”. However, not all acts that are dangerous to society are crimes and the person who commits them must bear criminal responsibility, and not every criminally responsible act must be punished. For that reason, based on the core content of criminal law, the article clarifies the proposed cases (possibilities) and typical forms of expression of crime from the starting point of “dangerous act(s) to society”. It sets out a number of problems and solutions, thereby raising scientific awareness and ensuring accurate and comprehensive handling of three root issues of criminal law - crime, criminal liability, and punishment. This contributes to the fight against crime in the new context.